LEVERAGE AND IPO PRICING: EVIDENCE FROM MALAYSIA - Chui Zi Ong; Rasidah Mohd-Rashid; Kamarun Nisham Taufil-Mohd (The International Journal of Banking and Finance, 2020)
The pricing of IPOs is a challenging task among underwriters as they require resources from firms. Contrary to the non-financial information presented in a prospectus to set an offer rice, pre-IPO accounting information could arguably influence IPO offer price. This study aims to investigate the relationship between leverage and IPO offer price. A crosssectional Ordinary Least Square (OLS) regression was implemented to investigate the relationship between leverage and offer price based on a sample of 129 Malaysian IPOs issued between January 2009 and December 2018. As a result, it was proven that leverage was negatively related to offer prices. Accordingly, it was proposed in the findings that fit, which issued higher leverages prior to IPO listing, often posed high financial risks. Subsequently, underwriters and issuers set a lower price for IPOs to compensate for a higher degree of information asymmetry among retail investors. Among the implications of this study’s findings include investor concerns on accounting information, especially leverage upon determining IPO value and IPO investment.